Çiftliks, landowners and rural producers : class relations in the Balkans (18th–19th Centuries) - Işıl, Ezgi Burcu. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2023., 2023)
This dissertation examines the rural society of the Ottoman Balkans, focusing on the districts of Manastır, İştip, and Pirlepe through the central themes of çiftlik production and inequality. The analysis mainly focuses on the property and labor relations between landowners and rural inhabitants by positing the çiftlik question in the broader framework of rural class structure and labor relations in the Ottoman Balkans in the 19th century. The main sources utilized in this study consist of income survey registers ("Temettuat Defterleri") of the districts under study. The analysis of the large-scale dataset obtained from these sources is combined with GIS analysis to demonstrate the diversity of settlement and production forms in a large geographical area. The thesis also touches upon several issues related to the rural structure and agrarian dynamics, including restriction of peasant mobility, imposition of corvee on agricultural producers, peasant poverty and indebtedness, appropriation of peasant land, and the turning of villages into çiftliks through incorporation into the study a variety of historical documents. In general, this dissertation combines different sources in order to portray the organization of the agricultural economy and the structure of the rural society of the Ottoman Balkans from the late 18th to the early 20th century from as many angles as possible by focusing on a selection of three districts -Manastır, İştip, and Pirlepe.
Keywords: Agriculture -- Economic aspects -- Turkey -- 18th century.; Agriculture -- Economic aspects -- Turkey -- 19th century.; Manastır (Bulgaria); Štip (North Macedonia); Pirlepe (North Macedonia)